Catalytic steam reforming of pyrolysis gas from plastic waste for syngas production - Foo, Thaddeus Jin Jun (Nanyang Technological University, 2021)
Humanity reliance on plastic has led to the current problem of dealing with the waste that is generated. Pyrolysis of plastics waste provides an alternative method of handling the waste besides using the conventional methods such as landfilling or incinerations. During pyrolysis of waste plastics, pyrolysis gas was obtained consisting mainly of hydrocarbons can be converted to useful syngas. Pyrolysis gas obtained through the process could be upgraded to synthetic gas via steam reforming (SR) reaction in the presence of a catalyst. SR reaction is important as it generates substantial amount of H2. This is subsequently used in the formation of ammonia and other chemicals. In addition, syngas produced during the reaction can be used for electricity generation which lessen the carbon footprint from conventional energy production such as burning of fossil fuel. Catalysts affect the conversion efficiency of steam reforming and the composition of the catalyst would determine the degree to which the reaction is affected. The pyrolysis gas was derived from mixed plastics and used as feedstock for the SR reaction. This study focuses on 4 types of Ni-based catalyst (Ni, Ni-CeO2, Ni-LaO1.5, Ni-WO3) and they were prepared via co-precipitation method. The metals of interest as promoter were Ce, La, and W. The prepared catalysts were evaluated in cofeeding SR of plastic pyrolysis gas. It was found that among the three promoters, W had a negative effect in terms of syngas production while Ce and La promoters were able to produce results similar to that of non-promoted catalyst. In addition, with the co-precipitation method, 4 types of Ni and Fe-based catalyst (Ni/Fe molar ratio = 1) are prepared for chemical looping steam reforming (CLSR) of the pyrolysis gas. The content of Ni and Fe was adjusted by changing the Al/(Ni+Fe) ratio. Concentrated H2 and syngas were obtained from the reduction (pyrolysis gas decomposition) and oxidation (steam gasification) reaction stages. The hydrocarbon conversion and gas productivity decreased as the ratio increased. The result is substantiated by the characterization of spent catalyst using XRD and FESEM in which the higher ratio of Al/(Ni+Fe) showed a reduction of active sites which inhibits the ability of the catalyst during the reaction. This study demonstrates the effects of promoters and the different Al ratios on the Ni-Fe-Al catalyst.